Size doesn´t matter—recircumscription of Microlejeunea (Lejeuneaceae, Porellales) based on molecular and morphological evidence - Dong, Shanshan; Schäfer-Verwimp, Alfons; Pócs, Tamás; Feldberg, Kathrin; Czumaj, Aleksandra; Schmidt, Alexander R.; Schneider, Harald; Heinrichs, Jochen (Phytotaxa, 2013)
Phylogenetic analyses of a three marker dataset of Lejeuneaceae (chloroplast genome rbcL gene and trnL-F region, and nuclear ribosomal ITS1-5.8S-ITS2 region) resolve the “Lejeunea complex” in three main lineages assigned here to Harpalejeunea, Lejeunea and Microlejeunea. The taxa Harpalejeunea fischeri, H. filicuspis, H. latitans and Pluvianthus squarrosus are nested in a clade with several representatives of Microlejeunea including the generitype M. africana, and are transferred to the latter genus. Harpalejeunea and Microlejeunea differ from Lejeunea by the presence of ocelli. Harpalejeunea has diverging, blunt underleaf lobes in contrast to the forward directed, blunt to acute underleaf lobes of Microlejeunea. Morphologically similar accessions of Microlejeunea form independent lineages. Drepanolejeunea vandenberghenii is newly reported for Madagascar, Malawi and Réunion.